Deletion of the non-adjacent genes UL148 and UL148D impairs human cytomegalovirus-mediated TNF receptor 2 surface upregulation - Le-Trilling, Vu Thuy Khanh; Maaßen, Fabienne; Katschinski, Benjamin; Hengel, Hartmut; Trilling, Mirko (Frontiers in Immunology, 2023)
Human cytomegalovirus (HCMV) is a prototypical β-herpesvirus which frequently causes morbidity and mortality in individuals with immature, suppressed, or senescent immunity. HCMV is sensed by various pattern recognition receptors, leading to the secretion of pro-inflammatory cytokines including tumor necrosis factor alpha (TNFα). TNFα binds to two distinct trimeric receptors: TNF receptor (TNFR) 1 and TNFR2, which differ in regard to their expression profiles, affinities for soluble and membrane-bound TNFα, and down-stream signaling pathways. While both TNF receptors engage NFκB signaling, only the nearly ubiquitously expressed TNFR1 exhibits a death domain that mediates TRADD/FADD-dependent caspase activation. Under steady-state conditions, TNFR2 expression is mainly restricted to immune cells where it predominantly submits pro-survival, proliferation-stimulating, and immune-regulatory signals. Based on the observation that HCMV-infected cells show enhanced binding of TNFα, we explored the interplay between HCMV and TNFR2. As expected, uninfected fibroblasts did not show detectable levels of TNFR2 on the surface. Intriguingly, however, HCMV infection increased TNFR2 surface levels of fibroblasts. Using HCMV variants and BACmid-derived clones either harboring or lacking the ULb’ region, an association between TNFR2 upregulation and the presence of the ULb’ genome region became evident. Applying a comprehensive set of ULb’ gene block and single gene deletion mutants, we observed that HCMV mutants in which the non-adjacent genes UL148 or UL148D had been deleted show an impaired ability to upregulate TNFR2, coinciding with an inverse regulation of TACE/ADAM17.